Open Trial of a Brief Imagery-Based Stabilization Psychotherapy for Adults with Acute Posttraumatic Stress Disorder - Son, Boyoung; Kim, Daeho; Lee, Hyunji; Min, Ji Young; Hong, Jiyoung (Yonsei medical journal, 2024)
Early intervention after trauma is needed for reduction in clinical distress and prevention of chronic posttraumatic stress disorder (PTSD). This study describes findings from an open pilot trial of a brief stabilization psychotherapy based on imagery techniques for adults with acute PTSD (i.e., within 3 months of onset). Four sessions of 60-minute individual psychotherapy were conducted on 18 participants with PTSD within 3 months after accidents, 15 of whom completed the treatment. The clinician-administered PTSD scale for Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5), the Hamilton Depression and Anxiety Rating Scales, and self-questionnaires were administered at pre-treatment, post-treatment, and 6-month follow-up. Eight (53.3%) of the 15 patients at post-treatment and 8 of the 9 patients at 6-month follow-up did not meet the DSM-5 criteria for PTSD. Reliable change of PTSD symptoms after treatment was observed in 6 of 15 (45.0%) patients at post-treatment and in 4 of 9 (45.0%) patients after 6 months. There was a significant decrease in PTSD, depression, anxiety, and impaired quality of life scores after treatment, and these gains were maintained after 6 months. No cases of exacerbated PTSD symptoms were observed among completers and non-completers. Our findings suggest that brief stabilization sessions are safe treatment options for acute PTSD (KCT0001918).